If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3(x-1)=8-3(x-3)
We move all terms to the left:
2-3(x-1)-(8-3(x-3))=0
We multiply parentheses
-3x-(8-3(x-3))+3+2=0
We calculate terms in parentheses: -(8-3(x-3)), so:We add all the numbers together, and all the variables
8-3(x-3)
determiningTheFunctionDomain -3(x-3)+8
We multiply parentheses
-3x+9+8
We add all the numbers together, and all the variables
-3x+17
Back to the equation:
-(-3x+17)
-3x-(-3x+17)+5=0
We get rid of parentheses
-3x+3x-17+5=0
We add all the numbers together, and all the variables
-12!=0
There is no solution for this equation
| 27a=3a+144 | | 0.2=0.9^t | | 30p=12p+144 | | 2(×+1)+1=1-2(x-3) | | 24s=8s+144 | | 5e=2e+51 | | 21t=11t+70 | | 3+m=40 | | 6a=a+315 | | (3x+15)=(-2x+30) | | 7t=t+84 | | 4×-7=3x+5 | | 2-1(5y-3)=0 | | 8s=5s+57 | | a(9)=a9-1+1/2 | | 9n=4n+135 | | 15a=11a+92 | | 3x+5+7x-12=8x-2x+1 | | w/12=35 | | 0.5x+17=4x+10 | | 11=6.9-x | | 4(z-45)=8(z-55) | | 30^30=(18^18)+(9x+4+18) | | (X+3)(4x+1)=0 | | 3(x-2)=55 | | 360=5x+2x+(x+12) | | 4-2u=16 | | 11=6.9+x | | 15-t=-5 | | 30^2=(18^2)+(9x+4+18) | | 0+0.7x=8-2x | | 5-s=15 |